(untitled) (Relevant Tomorrow / Aktualu rytoj, 2022)
The COVID-19 crisis became a great opportunity to spread populistic discourses that were usually accompanied by conspiracy theories. The article reveals a gradual process of politicization of the crisis by various Lithuanian populist actors, transforming the COVID-19 pandemic from a medical issue into a political one. Ernesto Laclau’s theory of populism combined with William Felstiner’s framework of politicization conceptualize these processes. The research showed that populist actors used a specific discourse dynamic to make the pandemic a political issue, moving from criticism of the specific measures to manage the pandemic, to an abstract and negative assessment of the situation as a whole.